Sistema Emagreça@Saudável para controle da obesidade em adultos - Barbosa, Maria Lúcia Kroeff; Zancan, Luciano; Zemor, Mario Figueiró; Roesler, Valter; da Costa, Marcia Rosa; Cazella, Sílvio César (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2018: Anais Estendidos do XXIV Simpósio Brasileiro de Sistemas Multimídia e Web, 2018)
This paper presents the Slim&Healthy system, focusing on the control of obesity in adults and aiming at the adoption of healthy habits. The system consists of two parts: a) an Android application on the client mobile device; b) an application on a server. The paper integrates different theories to increase user motivation, such as gamification, social networks, design heuristics for mobile devices and behavioral theories. It was performed an evaluation of the application interface through a questionnaire adherent to standards ISO 9241-11 and ABNT ISO/IEC 25062:2011, and the results are presented for discussion.